Optimization of Community Reading Garden Management in Improving Reading Culture - Septiarti, Serafin Wisni; Sujarwo, Sujarwo; Santi, Fitta Ummaya; Tristanti, Tristanti (Universitas Negeri Semarang, 2020)
TBM is more accurately called a reading facility in the middle of the community (community-based library) and is managed simply, and independently by the community concerned. This action research aims to (1) describe the management pattern of Community Reading Gardens as part of Omah Passionaon empowerment programs; (2) Explain the optimization of TBM management in its efforts to improve reading culture. Action research with a focus on optimizing TBM management is carried out using a diagnosis, planning, implementing action and evaluation model with Omah Passinaon managers as research subjects. Data or information is collected by interviewing techniques such as FGDs, observations on aspects of program management, activities to obtain a comprehensive picture of the potential, problems, needs for improvement and forms of action to optimize TBM management. The results of this study indicate that (1) TBM management emphasizes the competence of capable and skilled managers in building public awareness of the importance of reading culture, as well as the realization of TBM that has community appeal as a source of information in Bejiharjo tourism area. (2) Actions for optimizing TBM management in research include (a) Raising public awareness of reading fondness at Omah Passionaon, (b) partnerships with academics, universities, and private parties, (c) mentoring for pioneering TBMs that attract public interest in reading, (d) evaluation. TBM management can be effective must have partnerships from private or government institutions, besides that the manager also has good competence. The benefit of this research is to provide awareness to the community to read and motivation for TBM managers to seek partnerships with private and government institutions.